Potential Evapotranspiration in Merapi Aquifer System - Rahmawati, Novi; Rahayu, Kisworo; Arisanty, Deasy (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
Temperature variation due to climate change can give greatest impact on potential evapotranspiration. Increase of temperature in Yogyakarta Special Region can increase potential evapotranspiration. It is necessary to study potential evapotranspiration as one of indication impact of climate change to its potential evapotranspiration. Potential evapotranspiration (PET) can be estimated applying Hargreaves and Samani (1982) that requires limited meteorological parameter. Therefore, this research aims are: a) to analyze daily PET in 3 gauge station of Merapi Aquifer System, b) to analyze variation PET in the 3 gauge stations of Merapi Aquifer System. The largest values of PET is in Barongan station, while the lowest is in Adisucipto station. It is probably because Adisucipto station is located in urban and crowded areas. PET values are mostly 1.98 mm/day in rainy season, while 1.67 mm/day in dry season. Mostly, the correlation coefficient is low in dry season for Pluyon, Barongan and Adisucipto stations suggesting that drier and warmer temperature due to climate change do not have large impact to PET. The 5-month moving average trend also confirm the relatively stable line of PET variation from January 2005 to December 2016 reflecting that climate change do not greatly impact on PET in Merapi Aquifer System.